The Use of Dominance, Influence, Steadiness, and Compliance (DISC) Personality Test in the Assessment of Nurses’ Personal Characteristics - Aini, Qurratul; Dzakiyullah, Nur Rachman; Abdulamir, Mohammed (Fakultas Ilmu-ilmu Kesehatan, 2023)
A person's personality may indicate whether or not they indulge in unproductive behavior. An individual's work approach, performance limitations, and performance faults are directly correlated with his or her personality type. The Dominance, Influence, Steadiness, and Compliance (DISC) personality test is one of the instruments used to identify personality types in work behavior. The DISC test assists organizations in describing personality characteristics, making decisions, and communicating with team members and stakeholders. Organizations and managers are able to determine the strengths and weaknesses of the personality types of the individuals they employ using a personality assessment test. This study examined the predominant forms of work behavior exhibited by experienced nurses on the job. This involved 65 nurses from one of Central Java's Islamic hospitals. This study used the DISC profile to assess nurse’s personal characteristics. The results showed that 61% of respondents received the maximum possible score for Steadiness, according to the results of this study. They had a dependable, trustworthy, good listener, patient, empathetic, and cordial personalities, which qualified them for the nurse position. Overall, the nurses met the personal characteristics criteria to be a nurse.